Does the Increase in Renewable Energy Influence GDP Growth? An EU-28 Analysis - Daniela Nicoleta Sahlian (Energies, 2021)
The aim of our study was to analyze whether the increase in the use of renewable energy can help GDP growth. The research carried out shows that renewable energy has the ability to decrease or neutralize the negative impact of greenhouse gases (GHG), but also to maintain economic growth. We focused our analysis on the EU-28 as we know that the EU Commission’s aim, in the near future, is to join forces to reduce the GHG used and move to renewable sources. We used a panel analysis with data between 2000 and 2019 from all Member States, and our results showed that their economic growth is influenced positively by the production of renewable energy, the GHG per capita, and the GHG intensity per GDP.